Sample size calculations are poorly conducted and reported in many randomized trials of hip and knee osteoarthritis: results of a systematic review - Copsey, B; Thompson, J; Vadher, K; Ali, U; Dutton, SJ; Fitzpatrick, R; Lamb, S; Cook, JA (Elsevier, 2018)
Objectives To review the methodology and reporting of sample size calculations in a contemporary sample of trials in osteoarthritis. Study Design and Setting Randomized trials in hip and/or knee osteoarthritis published in 2016 were identified by searching MEDLINE, Cochrane library, CINAHL, EMBASE, PsycINFO, PEDro, and AMED until March 31, 2017. Data were extracted on study characteristics, methods used to calculate the sample size, and the reporting and justification of components used in the sample size calculation. We attempted to replicate the sample size calculation using the reported information. Results This review included 116 trials. Seventy-eight (67%, n = 78/116) reported a power calculation. Less than a quarter reported all core components of the sample size calculation (21%, n = 16/78). The sample size calculation was only reproducible in 53% of the trials that reported a power calculation (n = 41/78). The replicated calculation produced a sample size over 10% larger than the reported value in 12% of trials (n = 9/78). Insufficient information was reported to allow the sample size calculation to be replicated in a quarter of trials (27%, n = 21/78). Conclusion Sample size calculations in trials of hip and knee osteoarthritis are not adequately reported, and the calculation frequently cannot be reproduced.